Multinational corporations' post-Unocal liabilities for violations of international law - Hall, Sarah M (The George Washington international law review, 2002)
Until recently, the primary legal liabilities of US-based multinational corporations (MNCs) for their overseas operations consisted of US federal and state laws and the laws of the country that hosted their investments. In addition to these legal liabilities, the court of public opinion frequently has expressed a special distaste for MNCs and their profit-seeking overseas operations, and accordingly has imposed a set of extra-legal liabilities. But now there is a newly exhumed weapon against MNCs: the forum of US federal court and a thirty-three word federal statute enacted in 1789 called the Alien Tort Claims Act (ATCA). This note will discuss the new and emerging post-Unocal liabilities of MNCs for their activities abroad.